Analysis of Fraud Potential in Village Fund Management in the Digital Era - Edizon Mirino; Dian Ferriswara; Fedianty Augustinah; Sri Kamariyah (Dynamics Social : International Journal of Social Sciences and Communication, 2026)
Digital transformation in the public sector has significantly driven service innovations, particularly in pension administration for Civil Servants (ASN). This study aims to analyze the development of digital-based public service innovations in pension administration while identifying the benefits and challenges associated with their implementation. The research employs a Systematic Literature Review (SLR) method by examining relevant scholarly articles from national journals focusing on the digitalization of public services and pension systems. The literature selection process was conducted systematically to identify, evaluate, and synthesize key findings related to digital pension service innovations. The results indicate that digitalization through applications and electronic platforms enhances administrative efficiency, accelerates data verification, and improves the speed of pension fund disbursement. It also strengthens transparency and accountability while simplifying bureaucratic procedures and expanding service accessibility for retirees. However, several challenges remain, including low digital literacy among retirees, limited access to technological devices, and insufficient public awareness regarding digital service usage. The findings suggest that the success of digital-based public service innovations depends not only on technological availability but also on human resource readiness, institutional capacity, and the level of public acceptance. Therefore, a comprehensive strategy is required, including improving digital literacy, strengthening information technology infrastructure, and optimizing communication efforts to ensure effective adoption.